Nutritional diagnosis in a Conilon coffee plantation in the northern region of the Espírito Santo state - Fontana, Ademir; Pires, Ivne Franco; Partelli, Fábio Luiz; Campanharo, Alex; Rocha, Juan Ricardo; Rodrigues, Jéssica Dalazen (Revista Agrogeoambiental, 2023)
The soils of Coastal Tablelands are characterized by low natural fertility, which reinforces the importance of assessing soil fertility and leaf nutrition of crops. The objective of this study is to present a diagnosis of soil fertility and leaf nutrition of coffee plantations with Conilon from Coastal Tablelands in the northern area of the Espírito Santo state. A total of 49 soil samples were collected at a depth of 0-0.20 m and 49 leaf samples. In the soil, we can find Al3+, Ca2+, Mg2+, K+, (H+Al), SB, V, CTC, pH (water), P Mehlich-1, carbon (C), organic matter (MO), nitrogen (N), Cu2+, Fe2+, Mn2+, Zn2+, and in the leaves N, P, K, Ca, Mg, Cu, Fe, Mn and Zn contents. Soil fertility and leaf nutrition were diagnosed, followed by the identification of deficit elements after comparison with reference coffee crops. In the soil, most coffee plantations have low levels of MO, K, Ca, Mg, Fe, Al and (H+Al), P in excess, and the other attributes at medium levels. As for the leaves, most coffee plantations have low levels of N, P, K, Mg, Cu, Fe, and Zn, Mn at an adequate level and Ca at a high level. The soil and leaf elements evaluated are mostly at lower levels than the reference crops.